Chlorate adsorption from chlor-alkali plant brine stream - Lakshmanan, S. (IWA Publishing, 2017)
Chlorates are present in the brine stream purged from chlor-alkali plants. Tests were conducted using activated carbon from coconut shell, coal or palm kernel shell to adsorb chlorate. The results show varying levels of adsorption with reduction ranging between 1.3 g/L and 1.8 g/L. This was higher than the chlorate generation rate of that plant, recorded at 1.22 g/L, indicating that chlorate can be adequately removed by adsorption using activated carbon. Coconut based activated carbon exhibited the best adsorption of chlorate of the three types of activated carbon tested. Introducing an adsorption step prior to purging of the brine will be able to reduce chlorate content in the brine stream. The best location for introducing the adsorption step was identified to be after dechlorination of the brine and before resaturation. Introduction of such an adsorption step will enable complete recovery of the brine and prevent brine purging, which in turn will result in less release of chlorides and chlorates to the environment. © IWA Publishing 2017.